Predictive factors for exacerbation and re-exacerbation in chronic obstructive pulmonary disease: an extension of the Cox model to analyze data from the Swiss COPD cohort - Pascal Urwyler; Nebal Abu Hussein; Pierre O. Bridevaux; Prashant N. Chhajed; Thomas Geiser; Peter Grendelmeier; Ladina Joos Zellweger; Malcolm Kohler; Sabrina Maier; David Miedinger; Michael Tamm; Robert Thurnheer; et al. (Multidisciplinary Respiratory Medicine, 2019)
Abstract Background The Swiss COPD cohort was established in 2006 to collect data in a primary care setting. The objective of this study was to evaluate possible predictive factors for exacerbation and re-exacerbation. Methods In order to predict exacerbation until the next visit based on the knowledge of exacerbation since the last visit, a multistate model described by Therneau and Grambsch was performed. Results Data of 1,247 patients (60.4% males, 46.6% current smokers) were analyzed, 268 (21.5%) did not fulfill spirometric diagnostic criteria for COPD. Data of 748 patients (63% males, 44.1% current smokers) were available for model analysis. In order to predict exacerbation an extended Cox Model was performed. Mean FEV1/FVC-ratio was 53.1% (±11.5), with a majority of patients in COPD GOLD classes 2 or 3. Hospitalization for any reason (HR1.7; P = 0.04) and pronounced dyspnea (HR for mMRC grade four 3.0; P < 0.001) at most recent visit as well as prescription of short-acting bronchodilators (HR1.7; P < 0.001), inhaled (HR1.2; P = 0.005) or systemic corticosteroids (HR1.8; P = 0.015) were significantly associated with exacerbation when having had no exacerbation at most recent visit. Higher FEV1/FVC (HR0.9; P = 0.008) and higher FEV1 values (HR0.9; P = 0.001) were protective. When already having had an exacerbation at the most recent visit, pronounced dyspnea (HR for mMRC grade 4 1.9; P = 0.026) and cerebrovascular insult (HR2.1; P = 0.003) were significantly associated with re-exacerbation. Physical activity (HR0.6; P = 0.031) and treatment with long-acting anticholinergics (HR0.7; P = 0.044) seemed to play a significant protective role. In a best subset model for exacerbation, higher FEV1 significantly reduced and occurrence of sputum increased the probability of exacerbation. In the same model for re-exacerbation, coronary heart disease increased and hospitalization at most recent visit seemed to reduce the risk for re-exacerbation. Conclusion Our data confirmed well-established risk factors for exacerbations whilst analyzing their predictive association with exacerbation and re-exacerbation. This study confirmed the importance of spirometry in primary care, not only for diagnosis but also as a risk evaluation for possible future exacerbations. Trial registration Our study got approval by local ethical committee in 2006 (EK Nr. 170/06) and was registered retrospectively on ClinicalTrials.gov (NCT02065921, 19th of February 2014).